Nickel phosphide loaded polytriazine imide composite material as well as preparation method and application thereof
By designing nickel phosphide-supported polytriazineimide composite materials in photocatalysts, the chemical bonds and electronic interactions between nickel phosphide and polytriazineimide are used to regulate the activity of the active sites and solve the existing problems. The problems of low hydrogen peroxide generation efficiency and catalyst deactivation in photocatalytic technology have been achieved to achieve efficient and sustainable hydrogen peroxide production.
Patent Information
- Application Number
- CN202411918008.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-25
AI Technical Summary
In the existing photocatalytic technology, the activation intensity of the active sites of semiconductor photocatalysts is weak or too strong for molecular oxygen, resulting in low hydrogen peroxide generation efficiency and easy inactivation of active sites, reducing the service life of the catalyst material.
A kind of composite material of nickel-based nickelized load amine orramine is designed. The N-NI chemical key connection between nickel phosphate nanopritidal particles and polyrinelide carrons and metal-carrier electronic interaction are regulated. The activity of the point promotes the activation of molecular oxygen into hydrogen peroxide.
It improves the production efficiency of photocatalytic hydrogen peroxide, prolongs the service life of catalyst materials, and realizes green technology of high -efficiency production of hydrogen peroxide at normal temperature.
Smart Images

Figure CN119346179A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nickel-based catalyst materials, and in particular to a nickel phosphide-loaded polytriazine imide composite material and a preparation method and application thereof. Background Art
[0002] Hydrogen peroxide is a vital chemical reagent and industrial product, widely used in many fields. Hydrogen peroxide has strong oxidizing properties and weak acidity, and is widely used as a bleaching agent, chemical raw material, disinfectant and water purifier. In wastewater treatment and pollution control, hydrogen peroxide, as a strong oxidant, can effectively degrade organic pollutants in water bodies, and its only byproduct is water, so it is regarded as a green and environmentally friendly oxidant. In recent years, the global demand for hydrogen peroxide has grown steadily, mainly due to the promotion of environmentally friendly technologies, the increasing demand for cleaning and disinfection, and its wide application in industries such as electronic manufacturing, papermaking and water treatment. As the concept of sustainable development becomes more popular, hydrogen peroxide will have a wider application prospect in the future, providing important support for the green transformation of various industries.
[0003] Currently, more than 95% of hydrogen peroxide worldwide is produced by the anthraquinone process. This method uses anthraquinone molecules as a circulating carrier to generate hydrogen peroxide through catalytic hydrogenation and oxidation reactions. In this process, anthraquinone molecules can be recycled many times, have highly selective chemical reactions, and the generated hydrogen peroxide has high purity and is suitable for a variety of industrial uses. However, the anthraquinone process has the disadvantages of high energy consumption, high equipment cost and complex operation. The hydrogenation and oxidation reactions need to be carried out under high temperature and pressure and involve the use of hydrogen, which places extremely high technical requirements on the control of reaction conditions. Against the backdrop of growing global concern about climate warming and energy shortages, it has become particularly urgent to develop a green, efficient and sustainable hydrogen peroxide production technology.
[0004] Photocatalytic preparation of hydrogen peroxide has attracted widespread attention because of its cleanness, safety and low energy consumption. Among them, solar energy is used as the only energy input, and the abundant water and oxygen in nature are catalyzed to generate hydrogen peroxide through photocatalysts. However, the current photocatalytic hydrogen peroxide generation efficiency is low and cannot meet the needs of conventional applications. The main reason for limiting its generation efficiency is that the activation strength of the active sites of semiconductor photocatalysts for molecular oxygen is weak or too strong. On the one hand, it causes molecular oxygen to be unable to be activated and converted into superoxide free radicals, an intermediate of hydrogen peroxide. On the other hand, it causes molecular oxygen to be overactivated, resulting in the breaking of the OO bond of molecular oxygen, and also the inability to generate superoxide free radicals, an intermediate of hydrogen peroxide, resulting in low hydrogen peroxide production. In addition, the strong affinity of molecular oxygen to the active sites of semiconductor catalysts will cause oxidation of the active sites, resulting in inactivation of the active sites and reducing the service life of the catalyst material.
[0005] Based on the above background, how to design and develop an efficient semiconductor catalyst material with active sites that can efficiently activate molecular oxygen and have a moderate interaction between the active sites and molecular oxygen is the key to achieving efficient photocatalytic hydrogen peroxide generation. The design and synthesis method of this catalyst material will have significant energy and environmental significance, and also have great commercial prospects. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a nickel phosphide-loaded polytriazine imide composite material and a preparation method and application thereof.
[0007] The first object of the present invention is to provide a nickel phosphide-loaded polytriazine imide composite material, comprising a polytriazine imide carrier and nickel phosphide nanoparticles loaded on the surface of the polytriazine imide carrier; the nickel phosphide nanoparticles are connected to the surface of the polytriazine imide carrier through N-Ni chemical bonds, and metal-carrier electronic interactions are induced between the nickel phosphide nanoparticles and the polytriazine imide carrier.
[0008] In some embodiments of the present invention, the loading amount of the nickel phosphide nanoparticles is 0.5 ~ 5.0 wt.%. For example, it can be 0.5wt.%, 1wt.%, 1.5wt.%, 2wt.%, 2.5wt.%, 3wt.%, 3.5wt.%, 4wt.%, 4.5wt.%, 5wt.%, etc., or any interval value between any two values.
[0009] In some embodiments of the present invention, the method for preparing the nickel phosphide-loaded polytriazine imide composite material comprises the following steps: The molten salt mixture is mixed with a polytriazine imide material precursor, and subjected to a first heating and calcining in an inert atmosphere to obtain a first powder; The first powder is mixed with a nickel source solution, and solid-liquid separation is performed to obtain a solid phase, and the obtained solid phase is heated and calcined for a second time under a reducing atmosphere to obtain a second powder; The second powder and the phosphorus source are heated and calcined for the third time under an inert atmosphere to obtain the nickel phosphide-loaded polytriazine imide composite material.
[0010] In some embodiments of the present invention, the molten salt mixture is selected from two or more of LiCl, NaCl, KCl and CaCl2; The polytriazineimide material precursor is selected from one or more of urea, melamine, thiourea and dicyandiamide; The mass ratio of the polytriazine imide material precursor to the molten salt mixture is (0.1-0.2):1.
[0011] In some embodiments of the present invention, the conditions for the first heating and calcining are: 500-600°C for 4-8h. For example, the temperature may be 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, etc., or any interval between any two values; the holding time may be 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h; the heating rate is 1.5-5.0°C / min. For example, it may be 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min, etc., or any interval between any two values; The inert gas in the inert atmosphere is selected from nitrogen and / or argon.
[0012] In some embodiments of the present invention, the nickel source in the nickel source solution is selected from one or more of nickel nitrate, nickel chloride, and nickel acetylacetonate; The solvent of the nickel source solution is selected from one or more of water, ethanol or N,N-dimethylformamide; The concentration of the nickel source solution is 10.0 to 50.0 mmol / L. For example, it can be 10.0 mmol / L, 15.0 mmol / L, 20.0 mmol / L, 25.0 mmol / L, 30.0 mmol / L, 35.0 mmol / L, 40.0 mmol / L, 45.0mmol / L, 50.0 mmol / L, etc., or any interval value between any two values.
[0013] In some embodiments of the present invention, the dosage of the first powder in the nickel source solution is 1.0 to 10.0 g / L, illustratively, it can be 1.0 g / L, 2.0 g / L, 3.0 g / L, 4.0 g / L, 5.0 g / L, 6.0 g / L, 7.0 g / L, 8.0 g / L, 9.0 g / L, 10.0 g / L, etc., or any interval value between any two values; The reducing atmosphere includes hydrogen and an inert gas; The inert gas is selected from nitrogen and / or argon; The volume content of the hydrogen is 5.0-10.0%, illustratively, it can be 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%, etc., or any interval value between any two values; Conditions for the second heating and calcination: the heating temperature is 300 ~ 400 ° C, the heating time is 2 ~ 4 h, illustratively, the heating temperature can be 300 ° C, 310 ° C, 320 ° C, 330 ° C, 340 ° C, 350 ° C, 360 ° C, 370 ° C, 380 ° C, 390 ° C, 400 ° C, etc., the heating time is 2h, 2.5h, 3h, 3.5h, 4h, etc., and the heating temperature rise rate is 2 ~ 5 ° C / min, illustratively, it can be 2 ° C / min, 2.5 ° C / min, 3 ° C / min, 3.5 ° C / min, 4 ° C / min, 4.5 ° C / min, 5 ° C / min, etc., or any interval value between any two values.
[0014] In some embodiments of the present invention, the phosphorus source is selected from one or more of sodium hypophosphite, sodium hydrogen phosphate, and potassium hydrogen phosphate; Conditions for the third heating and calcination: heating temperature of 300 ~ 500 ° C, heating time of 0.5 ~ 3 h, illustratively, the heating temperature can be 300 ° C, 310 ° C, 320 ° C, 330 ° C, 340 ° C, 350 ° C, 360 ° C, 370 ° C, 380 ° C, 390 ° C, 400 ° C, 450 ° C, 500 ° C, etc., and the heating time is 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, etc.; the heating temperature rising rate is 2 ~ 5 ° C / min, illustratively, it can be 2 ° C / min, 2.5 ° C / min, 3 ° C / min, 3.5 ° C / min, 4 ° C / min, 4.5 ° C / min, 5 ° C / min, etc., or any interval value between any two values.
[0015] The second object of the present invention is to provide the use of the nickel phosphide-loaded polytriazine imide composite material in photocatalytic molecular oxygen activation conversion.
[0016] In some embodiments of the present invention, the product of the molecular oxygen activation conversion is hydrogen peroxide; The wavelength range of the light source in photocatalysis is 380 nm ~ 760 nm.
[0017] In the present invention, the regulation of active sites in nickel phosphide-loaded polytriazine imide composite materials and the metal-carrier electronic interaction induced between the nickel phosphide active sites and the carrier polytriazine imide form a regulation of the molecular oxygen activation conversion reaction. On the one hand, due to the presence of phosphorus atom ligands, the nickel phosphide active sites can adsorb molecular oxygen in a Pauling-type adsorption configuration, which inhibits the breakage of the molecular oxygen O-O bond to a certain extent, and promotes the activation and conversion of molecular oxygen into superoxide radicals, an intermediate of hydrogen peroxide. On the other hand, the metal-carrier electronic interaction induced between the nickel phosphide active sites and the carrier polytriazine imide induces the polytriazine imide carrier to transfer electrons to the nickel phosphide active sites, promotes the activation and conversion process of molecular oxygen and the generation of superoxide radicals, and improves the hydrogen peroxide yield.
[0018] The equation for the activation and conversion of molecular oxygen in the present invention is: O2+2H2O=2H2O2; The above technical solution of the present invention has the following advantages compared with the prior art: (1) The photocatalytic reaction of generating hydrogen peroxide has the advantages of being green, sustainable and low-cost. Compared with the traditional anthraquinone method, the system does not require large equipment and process investment and strict operating procedures. In the present invention, only sunlight is used as energy input, and oxygen and water are used as raw materials to produce hydrogen peroxide under the catalysis of nickel phosphide-supported polytriazine imide composite materials. The process is green and environmentally friendly, and the raw materials are widely available, realizing the preparation of hydrogen peroxide at room temperature and pressure.
[0019] (2) The nickel phosphide-loaded polytriazine imide composite material of the present invention has excellent photogenerated carrier efficiency separation capability, thereby improving the photocatalytic efficiency. The nickel phosphide active site has a moderate molecular oxygen activation ability due to its phosphorus atom ligand. Molecular oxygen interacts with the nickel phosphide in a Pauling-type adsorption configuration, promoting the activation and conversion of molecular oxygen into superoxide free radicals, an intermediate of hydrogen peroxide. At the same time, the metal-carrier electronic interaction between the nickel phosphide and the polytriazine imide carrier induces the polytriazine imide carrier to transfer electrons to the nickel phosphide, promoting the molecular oxygen activation and conversion process, promoting the activation and conversion of molecular oxygen into superoxide free radicals, and increasing the yield of hydrogen peroxide. At the same time, the nickel phosphide active site can activate water molecules to produce protons, promote the protonation process of superoxide free radicals, and increase the yield of hydrogen peroxide.
[0020] (3) The active sites in the nickel phosphide-loaded polytriazine imide composite material of the present invention can inhibit the breakage of the OO bond during the activation and conversion of molecular oxygen, have a high selectivity for hydrogen peroxide generation, and help to increase the hydrogen peroxide yield.
[0021] At the same time, the system is not limited by the site and can generate and utilize hydrogen peroxide in situ at the required production site. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein: Figure 1 HAADF-STEM images of the nickel phosphide-loaded polytriazine imide composite material prepared in Example 1 of the present invention and the polytriazine imide material in Comparative Example 2; wherein a is the nickel phosphide-loaded polytriazine imide composite material prepared in Example 1, and b is the polytriazine imide material in Comparative Example 2; Figure 2 XRD diagrams of the nickel phosphide-loaded polytriazine imide composite material prepared in Example 1 of the present invention and the polytriazine imide material in Comparative Example 2; Figure 3 The XPS graphs of the nickel phosphide-supported polytriazine imide composite material prepared in Example 1 of the present invention and the nickel-supported polytriazine imide material in Comparative Example 1; Figure 4 The performance of different catalyst materials in the present invention for photocatalytic activation and conversion of molecular oxygen to generate hydrogen peroxide; Figure 5 The performance of the nickel phosphide-supported polytriazine imide composite material prepared in Example 1 of the present invention and the nickel-supported polytriazine imide material in Comparative Example 1 is the photocatalytic activation and conversion of molecular oxygen to generate superoxide free radicals as a hydrogen peroxide intermediate; Figure 6 The present invention obtains the charge distribution of the nickel phosphide-loaded polytriazine imide composite material and the nickel-loaded polytriazine imide composite material during the molecular oxygen activation conversion process through first principle calculation (DFT); wherein a is the nickel phosphide-loaded polytriazine imide composite material, and b is the nickel-loaded polytriazine imide composite material; in the nickel phosphide-loaded polytriazine imide composite material, the nickel phosphide obtains electrons from the polytriazine imide material, indicating that the metal-carrier electronic interaction between the nickel phosphide and the polytriazine imide material induces the electrons to move to the nickel phosphide, which is beneficial to the molecular oxygen activation conversion and increases the hydrogen peroxide yield; in the nickel-loaded polytriazine imide composite material, the nickel is transferred to the triazine imide material carrier, which is not beneficial to the molecular oxygen activation conversion. DETAILED DESCRIPTION
[0023] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0024] Example 1
[0025] This embodiment provides a nickel phosphide-loaded polytriazine imide composite material and a preparation method and application thereof.
[0026] (I) A method for preparing a nickel phosphide-loaded polytriazine imide composite material, the specific steps are as follows: 1. Prepare a polytriazine imide material to obtain a first powder: fully grind and mix a molten salt mixture of LiCl (4.5 g) and KCl (5.5 g) and melamine (1.0 g) in a mortar; transfer the obtained solid powder of the mixture to a porcelain boat and heat and calcine it in a nitrogen atmosphere under the heating conditions of 550 °C for 4 h and a heating rate of 1.5 °C / min; wait until the temperature drops to room temperature to obtain the first powder.
[0027] 2. Dissolve nickel nitrate in deionized water to obtain a 10.0 mmol / L nickel source solution.
[0028] 3. Add 500 mg of the first powder into the obtained 50 mL of nickel source solution, stir and mix thoroughly, filter to obtain a solid, and then dry it in a vacuum drying oven (60 ° C) for 12 h to obtain a second powder.
[0029] 4. Transfer 200 mg of the second powder to a porcelain boat and heat and calcine in an argon-hydrogen mixed gas atmosphere to obtain a third powder; wherein the volume ratio of hydrogen is 5.0%, and the heating and calcination conditions are: heating temperature is 300 ℃, heating time is 4 h, and heating temperature rise rate is 2 ℃ / min.
[0030] 5. 50 mg of the third powder and 250 mg of sodium hypophosphite powder were transferred to a porcelain boat and heated and calcined under an argon atmosphere, wherein the heating and calcining conditions were as follows: heating temperature was 400 °C, heating time was 0.5 h, and heating temperature rise rate was 5 °C / min; the nickel phosphide-loaded polytriazine imide composite material was obtained; the loading amount of the nickel phosphide nanoparticles was 3.46 wt.%. The material was structurally characterized, and the results are shown in Figure 1 , Figure 2 and Figure 3 .
[0031] The HAADF-STEM image of the nickel phosphide loaded polytriazine imide composite material obtained in this example is as follows Figure 1 The XRD characterization results are shown in Figure 2 The XPS characterization results are shown in Figure 3 As shown. From the above figure, it can be seen that nickel phosphide is successfully loaded on the surface of the polytriazine imide carrier, and the loading of nickel phosphide has no significant effect on the crystal structure of the polytriazine imide carrier.
[0032] 2. Photocatalytic molecular oxygen activation and conversion reaction experiment The photocatalytic molecular oxygen activation and conversion performance of the obtained nickel phosphide-loaded polytriazine imide composite material was evaluated in a PCX-50C Discver multi-channel photocatalytic reaction device (Beijing Perfect Light Technology Co., Ltd., China), which is equipped with an LED light source with a wavelength of 380 nm to 760 nm. Within this range, it can accurately output the AM 1.5G solar spectrum to conduct photocatalytic molecular oxygen activation and conversion experiments. The evaluation results are the average of three tests.
[0033] Specific operation: 0.5 g / L of the nickel phosphide-loaded polytriazine imide composite catalyst of this embodiment was added to 30.0 mL of deionized water, and stirred for reaction for 1.0 h under the illumination of the photocatalytic device. Subsequently, 2.0 mL of the reaction suspension was taken out from the reaction container and filtered with a 0.22 μm water filter membrane. The resulting solution was measured for hydrogen peroxide concentration by DPD-POD colorimetric method. The experimental results are shown in Figure 4 As can be seen from the figure, the metal-carrier electronic interaction between nickel phosphide and polytriazine imide can effectively activate molecular oxygen and convert it into hydrogen peroxide.
[0034] Example 2
[0035] The preparation method is the same as that of Example 1, except that the nickel source solution is replaced by nickel chloride dissolved in deionized water to obtain a 25.0 mmol / L nickel source solution.
[0036] 2. Photocatalytic molecular oxygen activation and conversion reaction experiment The method for evaluating the photocatalytic molecular oxygen activation and conversion performance of the material in this embodiment is the same as that in Example 1. The efficiency of the molecular oxygen activation and conversion of the nickel phosphide-supported polytriazine imide composite catalyst to generate hydrogen peroxide is shown in FIG. Figure 4 shown.
[0037] Example 3
[0038] The preparation method is the same as that of Example 1, except that 50 mg of the third powder and 250 mg of sodium hypophosphite powder are transferred to a porcelain boat and heated and calcined under an argon atmosphere. The heating and calcination conditions are as follows: the heating temperature is 400°C, the heating time is 3.0 h, and the heating temperature rise rate is 5°C / min.
[0039] 2. Photocatalytic molecular oxygen activation and conversion reaction experiment The method for evaluating the photocatalytic molecular oxygen activation and conversion performance of the nickel phosphide-supported polytriazine imide composite catalyst obtained in this example is the same as that in Example 1. The efficiency of the molecular oxygen activation and conversion of the nickel phosphide-supported polytriazine imide composite catalyst to generate hydrogen peroxide is shown in FIG. Figure 4 shown.
[0040] Comparative Example 1 This comparative example uses a nickel-loaded polytriazine imide composite material as a control.
[0041] (I) Preparation method of nickel-loaded polytriazine imide composite material 1. Prepare a polytriazine imide material to obtain a first powder: fully grind and mix a molten salt mixture of LiCl (4.5 g) and KCl (5.5 g) and melamine (1.0 g) in a mortar; transfer the obtained solid powder of the mixture to a porcelain boat and heat and calcine it in a nitrogen atmosphere. The heating and calcination conditions are: 550 °C for 4 h, and the heating rate is 1.5 °C / min; wait until the temperature drops to room temperature to obtain the first powder.
[0042] 2. Dissolve nickel nitrate in deionized water to obtain a 10.0 mmol / L nickel source solution.
[0043] 3. Add 500 mg of the first powder into the obtained 50 mL of nickel source solution, stir and mix thoroughly, filter to obtain a solid, and then dry it in a vacuum drying oven (60 °C) for 12 h to obtain a second powder.
[0044] 4. 200 mg of the second powder was transferred to a porcelain boat and heated in an argon-hydrogen mixed gas atmosphere, wherein the volume ratio of hydrogen was 5.0%, the heating conditions were: heating temperature was 300 °C, heating time was 4 h, and heating rate was 2 °C / min; finally, a nickel-loaded polytriazine imide composite material was obtained, and the structure of the material was characterized. The results are shown in Figure 3 .
[0045] 2. Photocatalytic molecular oxygen activation and conversion reaction experiment The evaluation method of the photocatalytic molecular oxygen activation conversion performance of the material in this comparative example is the same as that in Example 1. The efficiency of the molecular oxygen activation conversion of the nickel-supported polytriazine imide composite catalyst to generate hydrogen peroxide is as follows: Figure 4 shown.
[0046] Comparative Example 2 This comparative example uses polytriazine imide material as a control.
[0047] (I) Preparation method of polytriazine imide material The molten salt mixture LiCl (4.5 g) and KCl (5.5 g) and melamine (1.0 g) were fully ground and mixed in a mortar; the obtained solid powder of the mixture was transferred to a porcelain boat and heated and calcined in a nitrogen atmosphere. The heating and calcination conditions were: 550 °C for 4 h, and the heating rate was 1.5 °C / min; when the temperature dropped to room temperature, the polytriazine imide material was obtained. The characterization results of the obtained material are shown in Figure 1 and Figure 2 , Figure 1 Compared with Figure a Figure 1 Figure b shows that many uniform particles are newly loaded on the polytriazine imide material, indicating that the nickel phosphide in Example 1 is successfully loaded.
[0048] 2. Photocatalytic molecular oxygen activation and conversion reaction experiment The method for evaluating the photocatalytic molecular oxygen activation conversion performance of the polytriazine imide material obtained in this comparative example is the same as that in Example 1. The efficiency of the catalyst for the activation conversion of molecular oxygen to generate hydrogen peroxide is as follows: Figure 4 shown.
[0049] Comparative Example 3 This comparative example uses phosphated polytriazine imide material as a control.
[0050] (I) Preparation method of phosphated polytriazine imide material A polytriazineimide material was prepared to obtain a first powder: a molten salt mixture of LiCl (4.5 g) and KCl (5.5 g) and melamine (1.0 g) were fully ground and mixed in a mortar; the obtained solid powder of the mixture was transferred to a porcelain boat and heated and calcined in a nitrogen atmosphere under the conditions of 550 °C for 4 h and a heating rate of 1.5 °C / min; the first powder was obtained when the temperature dropped to room temperature.
[0051] 50 mg of the first powder and 250 mg of sodium hypophosphite powder were transferred to a porcelain boat and heated and calcined in an argon atmosphere under the following heating conditions: heating temperature of 400°C, heating time of 0.5 h, and heating temperature rise rate of 5°C / min; the phosphated polytriazine imide material was obtained.
[0052] 2. Photocatalytic molecular oxygen activation and conversion reaction experiment The method for evaluating the photocatalytic molecular oxygen activation and conversion performance of the phosphorylated polytriazine imide material catalyst obtained in this comparative example is the same as that in Example 1. The efficiency of the molecular oxygen activation and conversion of the phosphorylated polytriazine imide material catalyst to generate hydrogen peroxide is as follows: Figure 4 shown.
[0053] from Figure 2 and Figure 3 It can be seen that, compared with Comparative Example 2, the characteristic peak corresponding to nickel phosphide appears in the phosphated polytriazine imide material catalyst obtained in Example 1, indicating that nickel phosphide exists in the composite material in Example 1.
[0054] from Figure 4It can be seen that, compared with the comparative examples, the nickel phosphide-loaded polytriazine imide composite materials prepared by different methods in Examples 1-3 all exhibited the activity of molecular oxygen activation and conversion into hydrogen peroxide, while the comparative examples 1-3 all exhibited lower activity of molecular oxygen activation and conversion into hydrogen peroxide, indicating that nickel phosphide is the key to the efficient generation of hydrogen peroxide.
[0055] from Figure 5 It can be seen that the nickel phosphide-loaded polytriazine imide composite material in Example 1 exhibits excellent activity in activating molecular oxygen to convert it into superoxide radicals, an intermediate of hydrogen peroxide, while the nickel-loaded polytriazine imide composite material in Comparative Example 1 exhibits lower activity in activating molecular oxygen to convert it into superoxide radicals, an intermediate of hydrogen peroxide, indicating that nickel phosphide is the main active site for activating molecular oxygen to form superoxide radicals. Due to the presence of phosphorus atom coordination, the nickel phosphide active site can moderately activate molecular oxygen to generate superoxide radicals, thereby resulting in higher molecular oxygen activation and conversion activity to generate hydrogen peroxide; while nickel, due to its excessive activation of molecular oxygen, causes the breakage of the OO bond of molecular oxygen and cannot generate superoxide radicals, further reducing the generation efficiency of hydrogen peroxide.
[0056] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A nickel phosphide-loaded polytriazine imide composite material, characterized in that: The invention comprises a polytriazine imide carrier and nickel phosphide nanoparticles loaded on the surface of the polytriazine imide carrier; the nickel phosphide nanoparticles are connected to the surface of the polytriazine imide carrier through an N-Ni chemical bond, and metal-carrier electronic interaction is induced between the nickel phosphide nanoparticles and the polytriazine imide carrier; the preparation method of the nickel phosphide loaded polytriazine imide composite material is characterized by comprising the following steps: The molten salt mixture is mixed with a polytriazine imide material precursor, and subjected to a first heating and calcining in an inert atmosphere to obtain a first powder; The first powder is mixed with a nickel source solution, and solid-liquid separation is performed to obtain a solid phase, and the obtained solid phase is heated and calcined for a second time under a reducing atmosphere to obtain a second powder; The second powder and the phosphorus source are heated and calcined for the third time under an inert atmosphere to obtain the nickel phosphide-loaded polytriazine imide composite material.
2. The nickel phosphide-loaded polytriazine imide composite material according to claim 1, characterized in that: The loading amount of the nickel phosphide nanoparticles is 0.5 wt.% to 5.0 wt.%.
3. The nickel phosphide-loaded polytriazine imide composite material according to claim 1, characterized in that: The molten salt mixture is selected from two or more of LiCl, NaCl, KCl and CaCl2; The polytriazineimide material precursor is selected from one or more of urea, melamine, thiourea and dicyandiamide; The mass ratio of the polytriazine imide material precursor to the molten salt mixture is (0.1-0.2):
1.
4. The nickel phosphide-loaded polytriazine imide composite material according to claim 1, characterized in that: The conditions of the first heating and calcining are: 500-600°C for 4-8 hours, and the heating rate is 1.5-5.0°C / min; The inert gas in the inert atmosphere is selected from nitrogen and / or argon.
5. The nickel phosphide-loaded polytriazine imide composite material according to claim 1, characterized in that: The nickel source in the nickel source solution is selected from one or more of nickel nitrate, nickel chloride, and nickel acetylacetonate; The solvent of the nickel source solution is selected from one or more of water, ethanol or N,N-dimethylformamide.
6. The nickel phosphide-loaded polytriazine imide composite material according to claim 1, characterized in that: The concentration of the nickel source solution is 10.0 ~ 50.0 mmol / L.
7. The nickel phosphide-loaded polytriazine imide composite material according to claim 1, characterized in that: The dosage of the first powder in the nickel source solution is 1.0 to 10.0 g / L; The reducing atmosphere includes hydrogen and an inert gas; The inert gas is selected from nitrogen and / or argon; The volume content of the hydrogen is 5.0 to 10.0%; The conditions for the second heating and calcination are: heating temperature is 300 ~ 400 ℃, heating time is 2 ~ 4 h, and heating temperature rise rate is 2 ~ 5 ℃ / min.
8. The nickel phosphide-loaded polytriazine imide composite material according to claim 1, characterized in that: The phosphorus source is selected from one or more of sodium hypophosphite, sodium hydrogen phosphate, and potassium hydrogen phosphate; The conditions for the third heating and calcination are: heating temperature is 300 ~ 500 ℃, heating time is 0.5 ~ 3 h, and heating temperature rise rate is 2 ~ 5 ℃ / min.
9. Use of the nickel phosphide-loaded polytriazine imide composite material according to any one of claims 1 to 8 in photocatalytic activation and conversion of molecular oxygen.
10. The use according to claim 9, characterized in that: The product of the molecular oxygen activation conversion is hydrogen peroxide; The wavelength range of the light source in photocatalysis is 380 nm ~ 760 nm.
Citation Information
Patent Citations
Preparation method of phosphorus-doped carbon nitride loaded nickel efficient catalyst and product and application thereof
CN111774084A
Nickel phosphide / carbon nitride visible-light-driven photocatalyst without noble metal loading and preparation method thereof
CN114588925A
Ni-Ni2P-Ni5P4 / g-C3N4 photocatalyst as well as preparation method and application thereof
CN116273124A